Особливості реалізації прокурором своїх процесуальних повноважень під час доказування на досудовому розслідуванні - Палюх, А. І. (Видавництво Львівської політехніки, 2015)
На підставі розгляду уявлень про доказування у кримінальному провадженні у КПК України розкрито особливості реалізації прокурором своїх повноважень під час доказування на досудовому розслідуванні. Розкрито сутність управлінських відносин між прокурором – процесуальним керівником досудового розслідування та слідчим. Сформульовано пропозиції щодо вдосконалення діяльності прокурора шляхом систематичного вивчення ним планів розслідування, що складає слідчий, та з урахуванням вказівок прокурора щодо кримінального провадження. На основе рассмотрения представлений о доказывании в уголовном производстве в УПК Украины раскрыты особенности реализации прокурором своих полномочий при доказывании на досудебном расследовании. Раскрыта сущность управленческих отношений между прокурором – процессуальным руководителем досудебного расследования и следователем. Сформулированы предложения по совершенствованию деятельности прокурора путем систематического изучения им планов расследования, составляемых следователем, и с учетом указаний по уголовному производству. On the basis of the consideration of representations of proving in criminal proceedings, the criminal procedural law of Ukraine, modern prosecutorial and investigative practices disclosed features of the implementation of its powers by the prosecutor in proving during the pre-trial investigation. Grounded inconsistency of views of individual scientists do not admit evidence of the actual data collected during the pretrial investigation. Based on the approach to the definition of proving in criminal proceedings as a cognitive activity, which includes both carried out in accordance with the criminal procedure law search and cognitive actions (investigating (search), tacit investigating (search)), mental operations to assess received information and argumentation of procedural decision by the investigator, the prosecutor, the investigating judge, the court, revealed the role of the prosecutor in the proving process, the essence of the management of relations between the prosecutor the head of procedural pre-trial investigation and the investigator. Formulated the proposals for improving the activity of the prosecutor through a systematic examination of the investigation plan, compiled by the investigator, and taking it into account during giving instructions on the criminal proceedings.
Особенности реализации прокурором своих процессуальных полномочий при доказывании на досудебном расследовании
Features of the implementation his procedural powers of the prosecutor at the pre-trial investigation of proof
Keywords: прокурор; прокурорський нагляд у формі процесуального керівництва досудовим розслідуванням; досудове розслідування; доказування; форма участі прокурора у доказуванні під час досудового розслідування; прокурорский надзор в форме процессуального руководства досудебного расследования; досудебное расследование; доказывание; форма участия прокурора в доказывании в ходе досудебного расследования.; prosecutor; public prosecutor's supervision in the form of a procedural manual pre-trial investigation; pre-trial investigation; evidence; form of participation of the prosecutor in proving in pre-trial investigation